2018
DOI: 10.1097/aud.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Self-Reported Daily-Life Fatigue, Hearing Status, and Pupil Dilation During a Speech Perception in Noise Task

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
118
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(138 citation statements)
references
References 57 publications
12
118
2
1
Order By: Relevance
“…This finding is in line with several previous observations demonstrating an enhanced pupil size when individuals listen under acoustic challenges (Zekveld et al, 2010;Koelewijn et al, 2014;Winn et al, 2015;Wendt et al, 2016;Miles et al, 2017). Acoustic degradation due to auditory peripheral damage is associated with similar effects on pupil dilation during speech comprehension: It is larger for older compared to younger adults (Ayasse and Wingfield, 2018), for older adults with hearing loss compared to those without (Ayasse and Wingfield, 2018; but see Koelewijn et al, 2017;Wang et al, 2018), and for people with cochlear implants compared to people without (Winn, 2016).…”
Section: Pupillometric Measuressupporting
confidence: 91%
“…This finding is in line with several previous observations demonstrating an enhanced pupil size when individuals listen under acoustic challenges (Zekveld et al, 2010;Koelewijn et al, 2014;Winn et al, 2015;Wendt et al, 2016;Miles et al, 2017). Acoustic degradation due to auditory peripheral damage is associated with similar effects on pupil dilation during speech comprehension: It is larger for older compared to younger adults (Ayasse and Wingfield, 2018), for older adults with hearing loss compared to those without (Ayasse and Wingfield, 2018; but see Koelewijn et al, 2017;Wang et al, 2018), and for people with cochlear implants compared to people without (Winn, 2016).…”
Section: Pupillometric Measuressupporting
confidence: 91%
“…Although as noted several studies using speech stimuli have examined effects of hearing impairment on task-related pupil dilation, few studies have examined effects of hearing on the BPD itself. Those that have, have produced mixed results (cf., Zekveld et al, 2011;Kramer et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because pupil size variation is the result of a complex interplay between the 29 parasympathetic and sympathetic system, pupillometry can also reveal aspects of 30 listening effort relating to fatigue, motivation and arousal [31][32][33][34]. For instance, Wang 31 et al [34] showed a negative correlation between the need for recovery and peak pupil 32 dilation relative the baseline (PPD), supporting the assumption that high fatigue could 33 be related to a reduced state of arousal (hence smaller pupillary response) [35].…”
mentioning
confidence: 99%